THE QUESTION "optimization" TAXATION IN UKRAINE - Мацелик, М. О.; Пригоцький, В. А. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2009)
In this article given a shot opening of legal «optimization» in taxation, and also possible negativeconsequences which can come at separate normatively using - legal acts, as by taxpayersby so authorized organ.